(untitled) (Journal of Atomic and Molecular Sciences, 2014)
Investigate the dissociation and ionization process of cyclopropanone molecules by using the Density functional method. Find the transition states of cyclopropanone molecule and ion, and get the products from transition state to isomer. At the same time, calculate frequency and energy. Confirm their transition states between the reactants and resultants through the Intrinsic Reaction Coordinates (IRC) calculation.